Intracardiac Inverse Potential Mapping Using the Method of Fundamental Solutions - Meng, Shu; Sunderland, Nicholas; Chamorro-Servent, Judit; Bear, Laura R.; Lever, Nigel A.; Sands, Gregory B.; LeGrice, Ian J.; Gillis, Anne M.; Zhao, Jichao; Budgett, David M.; Smaill, Bruce H. (Frontiers in Physiology, 2022)
Introduction: Atrial fibrillation (AF) is the most prevalent cardiac dysrhythmia and percutaneous catheter ablation is widely used to treat it. Panoramic mapping with multi-electrode catheters can identify ablation targets in persistent AF, but is limited by poor contact and inadequate coverage. Objective: To investigate the accuracy of inverse mapping of endocardial surface potentials from electrograms sampled with noncontact basket catheters. Methods: Our group has developed a computationally efficient inverse 3D mapping technique using a meshless method that employs the Method of Fundamental Solutions (MFS). An in-silico test bed was used to compare ground-truth surface potentials with corresponding inverse maps reconstructed from noncontact potentials sampled with virtual catheters. Ground-truth surface potentials were derived from high-density clinical contact mapping data and computer models. Results: Solutions of the intracardiac potential inverse problem with the MFS are robust, fast and accurate. Endocardial surface potentials can be faithfully reconstructed from noncontact recordings in real-time if the geometry of cardiac surface and the location of electrodes relative to it are known. Larger catheters with appropriate electrode density are needed to resolve complex reentrant atrial rhythms. Conclusion: Real-time panoramic potential mapping is feasible with noncontact intracardiac catheters using the MFS. Significance: Accurate endocardial potential maps can be reconstructed in AF with appropriately designed noncontact multi-electrode catheters.